Pengembangan Media Pembelajaran Siviorbox Pada Materi Nilai-Nilai Pancasila Untuk Siswa Kelas V SDN 1 Sarangmeduro Kabupaten Rembang - Muhamad Mujib; Nilamsari Damayanti Fajrin (Universitas Maritim AMNI Semarang, 2023)
This research was motivated by the lack of use of instructional media during the learning process, especially in the material on Pancasila values ​​in theme 1 sub-theme 1. Which found that classical learning completeness in Civics subjects on Pancasila values ​​only got a percentage of 60%. The purpose of this study was to determine the validity, practicality and effectiveness of the SIVIORBOX learning media. This development research uses the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The test subjects for this study were fifth grade students at SDN 1 Saarangmeduro, Rembang Regency. The validity of the SIVIORBOX learning media obtained from the results of expert validation obtained a percentage of the learning media validator by 88%, the language validator by 74%, the material validator by 96%, and the learning design validator by 77.3%. With an average of 88.83%. The practicality of the SIVIORBOX learning media was obtained from the results of the student response questionnaire and also the teacher's response questionnaire. in the small group test student response questionnaire obtained a percentage of 100% and in the large group trial obtained a percentage of 93.6%. Then the results of the teacher's response obtained a percentage of 100%. From the results of calculating student response questionnaires and teacher response questionnaires, an average of 98.4% was obtained. The effectiveness of the SIVORBOX learning media was obtained from the results of calculating student and teacher activity observation sheets. on the results of observations of student activity, a percentage of 93.71% was obtained and on the results of observations of teacher activity, a percentage of 100% was obtained. Then the average acquisition from the results of the questionnaire observing the activities of teachers and students was 96.85%. Then on student learning outcomes obtained classical mastery scores with a percentage of 94.73%